Fenestrated Screws Augmented With PMMA Increase the Pullout Strength of Sacral Pedicle Screws. Issue 3 (April 2017) - Colman, Matthew; Pond, Jonathan; Bachus, Kent; Lawrence, Brandon D.; Spiker, William R.; Brodke, Darrel S.
Abstract : Study Design: Biomechanics. Objective: The objective of this study was to compare the fixation in osteoporotic specimens of a bicortical sacral pedicle screw to the following constructs: a unicortical solid screw augmented with polymethylmethacrylate (PMMA) (TRACT), a unicortical fenestrated screw augmented with PMMA (FEN), and a bicortical screw/sacral alar screw combination (PED/ALA). Summary of Background Data: Rigid posterior sacral fixation of osteoporotic spines is problematic due to poor bone quality. Options to improve fixation include bicortical or tricortical screw trajectory, addition of S2 alar screws, or PMMA augmentation. Materials and Methods: Eleven osteoporotic cadaveric sacra were potted in 2-part filler compound. As a baseline fixation method, a 6.5-mm bicortical pedicle screw was placed into 1 pedicle of each sacra. The contralateral side was randomly assigned to receive a unicortical fenestrated 6.5-mm pedicle screw augmented with PMMA, a unicortical solid 6.5-mm pedicle screw augmented with PMMA, or a bicortical pedicle screw/alar screw construct. Pedicle screws were failed in cantilever pullout using a materials testing machine. Data were normalized into a test index by taking the ratio of the test screw pullout strength to the intraspecimen bicortical control screw pullout strength. Results: The fixation strengths as expressed by the test index of the TRACT, FEN, and PED/ALA groups were 101%, 157%, and 167%, respectively. Although there was no statistical difference detected between the FEN and PED/ALA groups, the TRACT group had a trend toward lower pullout strength than the FEN ( P =0.06) or PED/ALA (0.06) groups. Although underpowered, this study did not detect biomechanical inferiority for any of the 3 test configurations when compared with standard bicortical S1 screws. Conclusions: The data indicate that the fixation strength of a fenestrated, PMMA-augmented construct or a combined S1 pedicle/S2 alar screw construct may be better than either standard bicortical or unicortical PMMA screw-tract augmented screws.